A simple technique to improve performance of four-port wideband MIMO antenna using shorting pins - Anh Tran-Tuan; Thao Hoang-Thi-Phuong; Yem Vu-Van; Hung Tran-Huy (PLoS ONE, 2025)
This paper presents a four-port multiple-input multiple-output (MIMO) antenna with compact size, wideband operation, and high isolation characteristics. The wideband performance is achieved by generating two adjacent resonances, which are respectively produced by a half-wavelength slot and a metasurface (MS). Four MIMO elements are arranged in a 2 × 2 configuration with zero spacing between the MIMO elements to achieve the compact size feature. For mutual coupling reduction, the adjacent elements are positioned so that their polarizations are perpendicular. Meanwhile, the coupling between the opposite elements is suppressed with the aid of shorting pins. The final design has compact size of 1.08 λ × 0.89 λ × 0.07 λ and center-to-center element spacing of 0.35 λ, where λ is the free-space wavelength at 5.2 GHz. The measured operating bandwidth, in which the reflection and transmission coefficients are respectively smaller than –10 and –20 dB, is from 4.9 to 5.8 GHz. Across this band, the proposed design has peak broadside gain of 4.5 dBi and good MIMO diversity performance. Compared to other related works, the proposed design has advantages of wideband, high isolation, while keeping a compact size characteristic.